2017
DOI: 10.1159/000464436
|View full text |Cite
|
Sign up to set email alerts
|

Co-Activation of TGFβ and Wnt Signalling Pathways Abrogates EMT in Ovarian Cancer Cells

Abstract: Background/Aims: The aggressive property of ovarian cancer (OC) in terms of epithelial-mesenchymal transition (EMT), proliferation and metastasis are of major concern. Different growth factors including TGFβ are associated with regulating these molecular events but the underlying mechanisms remain unclear. The aim of this report is to decipher the regulation of EMT by co-activation of TGFβ and Wnt signalling cascades in gaining malignancy. Methods: The expression of the different components of signalling event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…It is well documented that TGF‐β signaling plays essential role in enamel development, and Wnt and TGF‐β signaling often synergize their function each other during embryonic development and organogenesis (DiRenzo et al, ; Guo et al, ; Mitra & Roy, ; Zhou, Eid, & Glowacki, ). Thus, it is very likely that GSK3β inactivation inhibits ameloblasts differentiation through synergizing TGF‐β signaling or promoting TGF‐β expression in ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that TGF‐β signaling plays essential role in enamel development, and Wnt and TGF‐β signaling often synergize their function each other during embryonic development and organogenesis (DiRenzo et al, ; Guo et al, ; Mitra & Roy, ; Zhou, Eid, & Glowacki, ). Thus, it is very likely that GSK3β inactivation inhibits ameloblasts differentiation through synergizing TGF‐β signaling or promoting TGF‐β expression in ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 A recent study suggested that Wnt signalling is related to the increased expression of Snail, mediating EMT in ovarian cancer cells. 51 Furthermore, Wnt signalling has been reported to increases Snail protein levels and activity by inhibit snail phosphorylation and eventually induced epithelial-mesenchymal transition in cancer cells. 52 However, how the Wnt/β-catenin signalling pathway to affect the expression pattern of snail has never been described.…”
Section: β-Catenin/snail Signalling Is Required For E2induced Emt Imentioning
confidence: 99%
“…OC cells were transfected with CD44s-overexpression clone or ESRP1-siRNA or treated with TGFβ1 and wound healing assay was performed as described previously. 26 Briefly, highly confluent OC cells were serum starved and the wound was made through the cell monolayer using a 200 µL pipette tip. Following this, the cells were washed twice with 1X PBS to remove the non-adherent cells.…”
Section: Wound Healing Assaymentioning
confidence: 99%